Graft‐related complications and biaxial tensiometry following experimental vaginal implantation of flat mesh of variable dimensions. (14th December 2012) - Manodoro, S; Endo, M; Uvin, P; Albersen, M; Vláčil, J; Engels, A; Schmidt, B; De Ridder, D; Feola, A; Deprest, J
Abstract : Objective: To compare the occurrence of graft‐related complications (GRCs) and biomechanical properties of meshes implanted vaginally and abdominally. Design: In vivo animal experiment. Setting: Centre for Surgical Technologies, Medical Faculty, KU Leuven, Belgium. Population: Twenty adult parous Texel ewes. Methods: Sheep were implanted with Gynemesh M, a 28‐g/m² polypropylene mesh reinforced with polyglecaprone fibres, under general anaesthesia. Dissection into the rectovaginal septum was performed to accommodate a flat 50 × 50 mm ( n  = 10) or 35 × 35 mm ( n  = 10) mesh, which was sutured to the underlying tissues. A 50 × 50 mm mesh was laid over a primarily sutured, full‐thickness, 40‐mm longitudinal abdominal wall incision. Sacrifice was at 60 days ( n  = 10) or 90 days ( n  = 5). Main outcome measures: The occurrence of exposure, the degree of contraction and examination of the biomechanical properties of explants with a minimum radius of 32 mm via biaxial tensiometry. Results: Insertion of a 50 × 50 mm mesh led to exposures in 30% (3/10) of cases, and the average contraction rate was 52 ± 14%. In the 35 × 35 mm implants, there were no exposures, and the contraction rate was 25 ± 26.3%. Vaginal explants with no GRCs and of sufficient size had biomechanical properties that were comparable with those of abdominal explants. Conclusion: Vaginal mesh insertion is associated with GRCs, such as exposure and contraction. Although other factors probably play a role, this study illustrates that mesh size may also induce these complications. In a vaginal surgery model, clinically occurring GRCs can be reproduced. In addition, biomechanics of uncomplicated vaginal explants are comparable with those measured on abdominal explants.